Narcolepsy – genes, infections and vaccines: the clues for a new autoimmune disease (2014)
a with disease rare a considered is narcolepsy, world suggesting, another to region one from varies prevalence Its]. 2[ In]. 1 [factors environmental and genetic of importance the strong its to due mostly, nature autoimmune an has colepsynar that suspected have clinicians and scientists years recent related immune in polymorphisms specific with association antigen leukocyte human of frequency allele the, Namely. genes ,[1% [99–82 is patients narcoleptic among 02:06*DQB1) HLA( Later. carriers are individuals healthy of% 38–12 only while and narcolepsy between associations additional found reports fact the, However]. 3) [TCR?., g.e (polymorphisms gene other twins monozygotic among concordance disease of rate the that autoimmune other in as, that suggests% 35 and% 20 between is autoimmune other in as, that suggests% 35 and% 20 [role key a play factors environmental a key role